KEDUDUKAN SAKSI MAHKOTA SEBAGAI ALAT BUKTI DALAM PUTUSAN BEBAS TERHADAP DELIK PENYERTAAN PEMBUNUHAN BERENCANA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 912/K/PID/2017) - Indra Dohara Siburian; Ade Adhari (Jurnal Hukum Adigama, 2021)
Crown witness in the Supreme Court Decision No. 2437 K / Pid.Sus / 2011 is defined as a witness who comes or is taken from one of the suspects or other defendants who jointly committed a criminal act. The position of crown witnesses in the criminal justice system in Indonesia has been very often considered and used by judges in deciding a case. This study analyzes the position of crown witnesses as evidence that becomes a consideration for judges in deciding cases. The research method used in this study is a normative legal research method with a research approach. The research approach used in this study is a statutory approach (Statute Approach) and a case approach (The Case Approach). Such as the case of premeditated murder in the Supreme Court Decision Number 912 / K / PID / 2017 which occurred in Makassar with the victim Giring. The murder perpetrators consisted of 3 people, but only 2 were convicted while 1 was acquitted. In this case the judge ignores and does not consider the testimony of the crown witness as evidence as his consideration in deciding a case. The position of the crown witness is very important in a case where the testimony of the crown witness is also the testimony of the witnesses which cannot be ignored by the judge according to the legal regulations in Indonesia which have regulated the position of the crown witness himself.